Coaching performance swimmers: A complex 'process' - Cross, N. (coachesinfo.com)
The coaching theory and applied literature highlights the importance of viewing sports coaching as a process (for an overview see Lyle 1999). The process is both multifaceted and multidisciplinary. As such, it requires the input of a variety of different disciplines and from a number of different specialists. When one considers the basic building blocks that are necessary for effective coaching behaviour, it becomes obvious that contributions to a swimmer's development may have to be made in a wide variety of areas. These may include inputs in the areas of technique (biomechanics and skill learning), physiology, psychology, nutrition, theoretical knowledge of the sport, lifestyle management (including time management) and even tactics. Any inputs will be complicated by the need for coaches also to address the differences between children and adults and between males and females. Obviously, some of these inputs can be further divided into specific areas for attention such as in strength conditioning, flexibility, aerobic capacity, sport medicine, practice organisation and management, and competition planning including responsibility for entries, travel and accommodation arrangements etc. In addition, altitude training, laws of the sport, ethics, monitoring techniques, peaking and tapering, detraining, communication and even safe working practice (including prevention of injuries and overtraining) should be considered. With a process of such complexity coaches need to plan, periodise and individualise the swimming programme with considerable care. Although they may not be responsible personally for providing all of the expertise in these areas, their overall coaching role and responsibility is to plan and co-ordinate the various contributions to each and every swimmer into an effective strategy for enhancing competitive performance.